Silent Cinema and the Politics of Space - Horak, Laura; Kapse, Anupama; Bean, Jennifer M., 1968- (Book collections on Project MUSE., 2014)
In this cross-cultural history of narrative cinema and media from the 1910s to the 1930s, leading and emergent scholars explore the transnational crossings and exchanges that occurred in early cinema between the two world wars. Drawing on film archives from around the world, this volume advances the premise that silent cinema freely crossed national borders and linguistic thresholds in ways that became far less possible after the emergence of sound. These essays address important questions about the uneven forces-geographic, economic, political, psychological, textual, and experiential-that un.